An unpleasant small-stock effect in manufacturing: the case of the dependent buyer. Issue 10 (10th October 2016) - Itzkowitz, Jennifer; Loviscek, Anthony
Abstract : Purpose: The purpose of this paper is to determine if there is a significant difference in the investment risks between small-cap manufacturers that heavily depend on one or a few buyers, referred to as "dependent-buyers, " and small-cap manufacturers that have a more diversified customer base. If there is a significant difference both statistically and economically, then investors need to be aware of the dependent-buyer effect in their security selection and portfolio construction efforts. Design/methodology/approach: Using large samples of firm-level data from 2000 through 2011, the authors employ standard risk estimation modeling to compute β s, idiosyncratic risks, and total risks of both dependent-buyer firms and firms with a more diversified customer base. Findings: The authors find that the β s, idiosyncratic risks, and total risks of dependent-buyer firms are much greater than that of firms not in dependent relationships. These differences are both statistically and economically significant. Research limitations/implications: Buyer-supplier relationships can change quickly, and so a firm that has a diversified base in one period, for example, could be a dependent-buyer in the next period. Much depends on the reporting accuracy of firms and the ability of the securities exchange commission (SEC) to track the relationships. Practical implications: First, the risk of individual small-cap stocks is likely to be greater than perceived from macro-level data, leading to the need for more securities if idiosyncratic risk is to be eliminated. Second, small-cap investors have the opportunity to enhance portfolio construction efficiency by referencing data published by the SEC. Third, most investors interested in small-cap manufacturing stocks should find it prudent to allocate a large percentage of their small-cap investments to an index fund. While this may sacrifice higher returns, it also reduces the probability of experiencing an unpleasant small-stock effect. Originality/value: This is the first study to show that the difference in investment risks between small-cap manufacturers that depend on one or a few firms for their outputs and small-cap manufacturers that have a well-diversified customer base is statistically and economically significant, information that should be valuable to investors in their security selection and portfolio construction efforts.